Letter from Georg Bredig to Max Bredig, February 14, 1938 - Bredig, Georg (1938)
Goeg Bredig (1868-1944) writes to his son, Max Bredig (1902-1977), who has recently immigrated to the U.S.A. Georg updates him on bills he received from the American Express Company, sending Max back issues of a journal, and inquiring about continuing to send scientific manuals and books to the U.S.A. Georg additionally advises Max on managing his workload and health, and suggests he settle a dispute with his former supervisor on good terms. Georg concludes the letter with updates on family members and well-wishes from relatives and friends in Germany.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Shipping; Emigration and immigration